2000
DOI: 10.1002/1529-0131(200008)13:4<191::aid-anr3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical analysis of a medial unloading brace for osteoarthritis in the knee

Abstract: Objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 9 publications
(9 reference statements)
4
75
2
4
Order By: Relevance
“…The mean value of 0.040 Nm/kg and the mean maximum value of 0.053 Nm/kg for this cohort correlate well with prior studies using different instrumented braces. Self et al indicated values of 0.038 and 0.050 Nm/kg [16], the values reported by Pollo et al were 0.071 and 0.133 Nm/kg [20], and the latest study compare favorably with the value of 10 percent found in this study. Larger effects with the brace calculated in some studies may reflect orthoses tightened so snugly that they would not be well tolerated by the patients in real world use.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The mean value of 0.040 Nm/kg and the mean maximum value of 0.053 Nm/kg for this cohort correlate well with prior studies using different instrumented braces. Self et al indicated values of 0.038 and 0.050 Nm/kg [16], the values reported by Pollo et al were 0.071 and 0.133 Nm/kg [20], and the latest study compare favorably with the value of 10 percent found in this study. Larger effects with the brace calculated in some studies may reflect orthoses tightened so snugly that they would not be well tolerated by the patients in real world use.…”
Section: Discussionsupporting
confidence: 76%
“…Contradictory results from other studies [14][15][16] may be an artifact of different investigation approaches (e.g., use of instrumented braces, unrealistically tight adjustments of the braces). Results from previous studies on the effect of braces on knee axis movements are also equivocal.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, instructions on proper use of a cane on the side contralateral to the arthritic knee joint can be used as an early offloading strategy, by shifting a portion of the body mass off the symptomatic knee tissues during weight-bearing activities such as walking. 107,125 Full-length laterally wedged insoles 45,[76][77][78] or valgus knee bracing 46,120,170,197 may also be effective in modifying the tibiofemoral joint angle and the dynamic loading of the knee joint, thereby decreasing medial compartment compressive loads. Additionally, gait retraining strategies to reduce walking speed, especially in patients with less severe disease, 139 could be an effective offloading approach on a short-term basis.…”
Section: Short-term Treatment Optionsmentioning
confidence: 99%